2022
DOI: 10.1186/s12906-022-03639-5
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemistry, anti-diabetic and antioxidant potentials of Allium consanguineum Kunth

Abstract: Aim The study was planned to investigate the phytochemicals, antidiabetic and antioxidant studies of A. consanguineum. Methods The preliminary studies were performed on crude extract and different solvent fractions. Based on the potency, the chloroform fraction was semi-purified to phyto-fractions CHF-1 – 5. Furthermore, CHF-3 was subjected to isolation of pure compounds using column chromatography. The α-glucosidase, α-amylase and antioxidant assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Subsequently, 2 mg/kg oral glucose was administered to each animal. Blood glucose was monitored at different times from (0 to120 min) after administration of glucose (Mahnashi et al 2022a ).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, 2 mg/kg oral glucose was administered to each animal. Blood glucose was monitored at different times from (0 to120 min) after administration of glucose (Mahnashi et al 2022a ).…”
Section: Methodsmentioning
confidence: 99%
“…Idris et al (2022) [42] discovered that methanol extract from the leaves of the Rhodomyrtus tomentosa plant has antidiabetic effects of 82.41 ± 2.21% against α-amylase inhibition and 81.91 ± 1.09% against αglucoamylase inhibition. Methanol extracts from the Allium consanguineum plant inhibited α-amylase at concentrations of 62.5, 125, 250, 500, and 1000 μg/mL, which was 29.88 ± 0.89%, 42.78 ± 0.45%, 47.44 ± 0.86%, 64.72 ± 0.89%, and 75.29 ± 0.64% [43].…”
Section: -5-antidiabetic Testmentioning
confidence: 97%
“…Recently, edible and hydroponically grown Lactuca sativa soil have been reported to substantially reduce blood glucose levels in diabetic rats besides in vitro α-glucosidase inhibition activity [ 63 ]. The crude extract and two isolated compounds Coniferol (1) and dillapiole (2) (from chloroform phyto-fractions) of Allium consanguineum were investigated for their hypoglycemic effects [ 64 ]. The in vivo studies revealed that two compounds, coniferol and dillapiole, substantially lower blood glucose levels in albino mice.…”
Section: Plant Extracts As α-Glucosidase Inhibitor Sourcesmentioning
confidence: 99%